The landscape of epilepsy-related GATOR1 variants - Baldassari, Sara; Picard, Fabienne; Verbeek, Nienke E; van Kempen, Marjan; Brilstra, Eva H; Lesca, Gaetan; Conti, Valerio; Guerrini, Renzo; Bisulli, Francesca; Licchetta, Laura; Pippucci, Tommaso; Tinuper, Paolo; et al. (Genetics in medicine, 2019)
PURPOSE: To define the phenotypic and mutational spectrum of epilepsies related to DEPDC5, NPRL2 and NPRL3 genes encoding the GATOR1 complex, a negative regulator of the mTORC1 pathway METHODS: We analyzed clinical and genetic data of 73 novel probands (familial and sporadic) with epilepsy-related variants in GATOR1-encoding genes and proposed new guidelines for clinical interpretation of GATOR1 variants. RESULTS: The GATOR1 seizure phenotype consisted mostly in focal seizures (e.g., hypermotor or frontal lobe seizures in 50%), with a mean age at onset of 4.4 years, often sleep-related and drug-resistant (54%), and associated with focal cortical dysplasia (20%). Infantile spasms were reported in 10% of the probands. Sudden unexpected death in epilepsy (SUDEP) occurred in 10% of the families. Novel classification framework of all 140 epilepsy-related GATOR1 variants (including the variants of this study) revealed that 68% are loss-of-function pathogenic, 14% are likely pathogenic, 15% are variants of uncertain significance and 3% are likely benign. CONCLUSION: Our data emphasize the increasingly important role of GATOR1 genes in the pathogenesis of focal epilepsies (>180 probands to date). The GATOR1 phenotypic spectrum ranges from sporadic early-onset epilepsies with cognitive impairment comorbidities to familial focal epilepsies, and SUDEP.
Keywords: multiproteinové komplexy; represorové proteiny; záchvaty; Male; Pedigree; Child, Preschool; Genetic Predisposition to Disease; rodokmen; DNA Copy Number Variations; Genetic focal epilepsy; mutace ztráty funkce; Adolescent; Infant; Loss of Function Mutation; Child; Tumor Suppressor Proteins; SUDEP; proteiny aktivující GTPasu; mutace INDEL; signální transdukce; dítě; mužské pohlaví; variabilita počtu kopií segmentů DNA; Seizures; Signal Transduction; epilepsie; nádorové supresorové proteiny; mladiství; novorozenec; předškolní dítě; DEPDC5; mTORC1 pathway; mTORC1; GTPase-Activating Proteins; lidé; ženské pohlaví; Humans; Infant, Newborn; kojenec; Repressor Proteins; Brugadův syndrom; Focal cortical dysplasia; INDEL Mutation; Epilepsy; Female; Mechanistic Target of Rapamycin Complex 1; Brugada Syndrome; genetická predispozice k nemoci; Multiprotein Complexes